Oxophilic Ce single atoms-triggered active sites reverse for superior alkaline hydrogen evolution - Fengyi Shen; Zhihao Zhang; Zhe Wang; Hao Ren; Xinhu Liang; Zengjian Cai; Shitu Yang; Guodong Sun; Yanan Cao; Xiaoxin Yang; Mingzhen Hu; Zhengping Hao; et al. (Nature Communications, 2024)
Abstract The state-of-the-art alkaline hydrogen evolution catalyst of united ruthenium single atoms and small ruthenium nanoparticles has sparked considerable research interest. However, it remains a serious problem that hydrogen evolution primarily proceeds on the less active ruthenium single atoms instead of the more efficient small ruthenium nanoparticles in the catalyst, hence largely falling short of its full activity potential. Here, we report that by combining highly oxophilic cerium single atoms and fully-exposed ruthenium nanoclusters on a nitrogen functionalized carbon support, the alkaline hydrogen evolution centers are facilely reversed to the more active ruthenium nanoclusters driven by the strong oxophilicity of cerium, which significantly improves the hydrogen evolution activity of the catalyst with its mass activity up to −10.1 A mg−1 at −0.05 V. This finding is expected to shed new light on developing more efficient alkaline hydrogen evolution catalyst by rational regulation of the active centers for hydrogen evolution.